The Influence of Digital Financial Services on the Financial Inclusion by Commercial Banks in Cameroon - Beloke, Ngwengeh Brendaline (European Scientific Journal, ESJ, 2023)
Every nation needs a vibrant and strong banking system for growth and development. Banks are expected to move with time and adapt with the fast changes in technological advancement. Banks will only have to adapt to technological changes or go bankrupt. They must meet the unending needs and expectations of their customers and the society at large. Today, banks have a role in enhancing their own quota in financial inclusion (Social Performance) through the provision of digital financial services which is defined as the formal provision of banking services to the unbanked. This is a very rare area in academic literature as most studies focused on the financial performances of banks leaving out their efforts played to achieve financial inclusion an aspect of social performance to their credit. This paper sought to determine the influence of Digital Financial Services on the Performance of Commercial Banks in Cameroon. Specifically, it assesses the influence of Digital Savings Services, Digital Transfer Services, Digital Withdrawal Services and Digital Payment Services of commercial banks on their social performance (financial inclusion). Primary data was obtained through the administration of questionnaires and the average responses of four bank staff at management levels of the headquarters of each of the 10 commercial banks under study in Cameroon were used. After testing for validity, reliability, multicollinearity and heteroskedasticity and using the Feasible Generalised Least Square (FGLS) estimation technique, the following were the findings. Results revealed that, digital transfers’ services, digital savings services, and digital withdrawals services, positively influence financial inclusion by commercial banks with only digital savings services being statistical significant. Digital payment services had a negative and insignificant influence on financial inclusion fostered by banks in Cameroon. In conclusion, digital financial services of commercial banks influence banks’ social performance. This paper therefore recommended that management of banks and policy makers in the banking industry should consider investing in robust digital financial services, so as to enhance access to their service and to contribute their own quota in ensuring the unbanked have access to formal financial services. This will have a ripple effect on the sustainable growth and development of the economy given the vital role banks play in every nation.